P701 Compositional and functional alterations of the gut microbiome are associated with impaired intestinal permeability in healthy relatives of patients with Crohn's disease. (21st January 2022) - Leibovitzh, H; Lee, S H; Xue, M; Raygoza Garay, J A; Hernandez-Rocha, C; Madsen, K L; Meddings, J B; Guttman, D S; Espin-Garcia, O; Smith, M I; Goethel, A; Moayyedi, P; et al.
Abstract: Background: The gut microbiome may play a role in gut barrier homeostasis including epithelial barrier integrity and function. However, data are scarce and limited to animal studies. We aimed to assess if alterations in the gut microbiome are associated with altered intestinal permeability. Methods: We utilized the Genetic Environmental Microbial (CCC GEM) cohort of healthy first-degree relatives of patients with Crohn's disease. Gut barrier function was assessed using the ratio of urinary fractional excretion of lactulose to mannitol (LMR). Stool bacterial DNA was extracted and sequenced for the V4 hypervariable region of the 16S rDNA gene using MiSeq and processed using QIIME2. PICRUSt2 was used to impute Microbial functions. In order to identify robust associations, the overall cohort was divided based on geographic region into a North American discovery cohort (n=2, 472) and non-North American external validation cohort (n=655). LMR>0.025 was defined as abnormal. LMR-microbiome associations were assessed using generalized estimating equation multivariable regression model and Random Forest (RF) classifier algorithm. q<0.05 was considered significant when multiple tests were performed. Results: The median age of the entire cohort was 17.0 years [IQR 12.0; 24.0], 52.6% were females and 25.4% had LMR>0.025. In the discovery cohort, subjects with LMR>0.025 had markedly reduced alpha diversity (Chao1 index, estimate= -0.0037, p=4.0e-04) and altered beta diversity (Bray-Curtis dissimilarity index, PERMANOVA: pseudo-F statistic = 2.99, p=1.0e-03). Eight bacterial genera and 52 microbial pathways were identified to be associated with LMR>0.025 (q<0.05). The compositional associations were replicated in four genera ( Adlercreutzia [odds ratio(OR)=0.74, 95% confidence interval (CI) 0.6–0.91], Clostridia-UCG-014 [OR=0.71, 95%CI 0.59–0.86], Clostridium-sensu-stricto-1 [OR=0.75, 95%CI 0.61–0.92] and Colidextribacter [OR=1.65, 95%CI 1.2–2.26]). The pathway associations were replicated in eight pathways (biosynthesis of glutamate [OR=0.4, 95%CI 0.21–0.74], tryptophan [OR=0.06, 95%CI 0.01–0.27] and threonine [OR=0.038, 95%CI 0.003–0.41], among others). Bacterial community composition was associated with gut barrier homeostasis as defined by the RF analysis (p= 1.4e-6). Conclusion: Gut microbiome community composition and microbial pathways are associated with gut barrier function. These findings may identify microbial targets that enhance barrier function.